Perlindungan Hukum bagi Perempuan Korban ‎Kekerasan dalam Rumah Tangga Perspektif Hukum ‎Islam - Amirul ikhsan (Al-Jinayah: Jurnal Hukum Pidana Islam, 2016)
Abstract: This article discusses the legal protection for women-victims of domestic violence within the perspective of Islamic law. Legal protection for women-victims of domestic violence is clearly regulated in Law No. 23 of 2004. It should be recognized that the presence of the law is to open a way for unfolding of domestic violence and to safeguard the civil rights of victims, where it was previously considered as a private area that no one outside the household environment entries. On the perspective of Islamic law, legal protection in the Law number 23 of 2004 has been consistent with the objectives of shariah. It is to enforce Islamic law to gain the pleasure of Allah. In this context, husband and wife should complement each other and work together in building a harmonious household.Keywords: Legal protection, victims, domestic violence, Islamic law. Abstrak: Artikel ini membahas tentang perlindungan hukum bagi perempuan korban kekerasan dalam rumah tangga perspektif hukum Islam. Perlindungan hukum bagi perempuan korban kekerasan dalam rumah tangga (KDRT) diatur dalam undang-undang nomor 23 tahun 2004 (UUPKDRT), harus diakui kehadirannya membuka jalan bagi terungkapnya kasus KDRT dan upaya perlindungan hak-hak korban, yang pada awalnya KDRT dianggap sebagai wilayah privat yang tidak seorang pun di luar lingkungan rumah tangga dapat memasukinya. Perspektif hukum Islam, perlindungan hukum dalam Undang-Undang nomor 23 tahun 2004 (UUPKDRT) telah sesuai dengan tujuan syariah yaitu untuk menegakkan syariat Islam, menuju ridha Allah swt, suami dan istri harus saling melengkapi dan bekerja sama dalam membangun rumah tangga yang harmonis menuju derajat takwa.Kata Kunci: Perlindungan hukum, korban, kekerasan dalam rumah tangga, hukum Islam.